Synthesis of Superabsorbent Hydrogels Consisted of Pectin and Poly(methacrylonitrile) for Drug Delivery Systems - Sadeghi, Mohammad; Gudarzi, Anahita; Safari, Soudeh; Shahsavari, Hadis; Sadeghi, Hossein (Asian Journal of Chemistry, 2013)
In the present paper, attention is paid to synthesize and evolution swelling behaviour of a superabsorbent hydrogel based on pectin and polyacrylonitrile. The physical mixture of pectin and polyacrylonitrile was hydrolyzed by NaOH solution to yield pectin-poly(sodium acrylate-co-acrylamide) superabsorbent hydrogel. the structure of the product was established using FTIR and SEM and TGA spectroscopies of initial substrates and superabsorbent hydrogel, respectively. The pectin-poly(sodium acrylate-co-acrylamide) hydrogel exhibited a pH-responsiveness character so that a swelling-deswelling pulsatile behaviour was recorded at pHs 1.6 and 7.4.